PENGARUH NILAI KONSUMSI TERHADAP MINAT BELI LAGU DIGITAL BTS PADA KOMUNITAS FANDOM ARMY - Langgeng Irma Salugiasih; Tandiyo Pradekso; Joyo Nur Suryanto Gono (Interaksi Online, 2023)
IFPI data shows a decline in global recorded music revenue from permanent digital download channels since 2014, while revenue from streaming channels has increased rapidly. In the midst of this phenomenon, BTS digital song sales are still producing brilliant achievements in the international music market. Consumption in the fandom community is known to have its own characteristics. This study aims to find out how consumption values influence ARMY interested in purchasing BTS digital songs. Product consumption values consist of functional value, social value, emotional value, epistemic value, and conditional value. These consumption values are proposed in Consumption Value Theory, which assumes that product choice behavior is influenced by one or all of the consumption values. Research into song buying has been around for a long time, but it has focused on emotional loyalties with artists and the effects of using audio streaming websites. This research is an explanatory research type. The sampling technique used non-random sampling with 112 research subject, male and female following ARMY fanbase group aged 20–30 years who had heard BTS digital songs. Testing were carried out using multiple linear analyses. Hypothesis testing shows effect of simultaneous consumption value on song purchase intention. This value is then explored in relation to the fan community when creating marketing strategies to create song success.